Sorafenib Prevents Escape from Host Immunity in Liver Cirrhosis Patients with Advanced Hepatocellular Carcinoma - Hidenari Nagai; Takanori Mukozu; Daigo Matsui; Takenori Kanekawa; Masahiro Kanayama; Noritaka Wakui; Kouichi Momiyama; Mie Shinohara; Kazunari Iida; Koji Ishii; Yoshinori Igarashi; Yasukiyo Sumino (Clinical and Developmental Immunology)
Purpose. It has been reported that Th2 cytokines downregulate antitumor immunity, while activation of type T cells promotes antitumor immunity. The aim of this paper was to evaluate host immunity in liver cirrhosis (LC) patients with advanced hepatocellular carcinoma (aHCC) receiving sorafenib therapy. Methods. Forty-five adult Japanese LC patients received sorafenib for aHCC between 2009 and 2011 at our hospital. Sorafenib was administered at a dose of 200–800 mg/day for 4 weeks. Blood samples were collected before and after treatment. Results. Eleven patients were treated with sorafenib at 200 mg/day (200 group), 27 patients received sorafenib at 400 mg/day (400 group), and 7 patients were given sorafenib at 800 mg/day (800 group). There was no significant change in the percentage of Th1 cells after treatment in any group. However, the percentages of Th2 cells and regulatory T cells were significantly decreased after treatment in the 400 group and 800 group compared with before treatment, although there was no significant change after treatment in the 200 group. Conclusions. These results indicate that treatment with sorafenib might induce Th1 dominance and prevent the escape of tumor cells from the host immune system in LC patients with aHCC.